Profile of co-occurring or secondary infections among COVID-19 patients with HBOT: a single-center retrospective study - Yu, Peixia; Wang, Hairu; Li, Ziyang; Zhang, Junyan; Wei, Shuang; Xue, Zhifeng; Zhang, Bozheng; Mei, Qi; Wang, Zhengtao; Zhao, Yani; Niu, Qing; Wang, Pingzhi (The Journal of Infection in Developing Countries, 2024)
Introduction: This study was designed to describe the profile of co-occurring or secondary infections in hospitalized coronavirus disease 2019 (COVID-19) patients undergoing hyperbaric oxygen therapy (HBOT) and those without. Methodology: Out of 716 COVID-19 patients, 79 cases of co-occurring or secondary infections were included. These patients were categorized into two groups based on their usage of HBOT. The basic information and laboratory examinations, especially pathogen-related results were collected from the medical records. The rate of co-occurring or secondary infections, distribution of pathogens, infection sites, and results of antimicrobial susceptibility testing were analyzed. Results: Among the 79 COVID-19 patients examined, there were 73 cases of infections, including 58 co-occurring infections, 14 secondary infections, and 1 mixed infection in the non-HBOT group. There were 6 cases with co-occurring or secondary infections in the HBOT group. Influenza virus was predominant in the co-occurring or secondary infections of COVID-19 patients, but it was not detected in patients undergoing HBOT. Klebsiella pneumoniae, Corynebacterium striatum, and Acinetobacter baumannii were the main strains isolated among patients with HBOT. The multidrug-resistant organisms (MDROs) strains of Escherichia coli, Klebsiella aerogenes, Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecium were detected from COVID-19 patients treated with HBOT. Conclusions: This study described the profile of in-hospital co-occurring or secondary infections in COVID-19 patients from North China. Management of the co-occurring or secondary infections, especially MDROs infections treated with HBOT, including but not limited to COVID-19, should be strengthened.